Observation and Simulation of Solid Sedimentary Flux: Examples From Northwest Africa - Lodhia, Bhavik; Roberts, G.G.; Fraser, A.J.; Jarvis, J.; Newton, R.; Cowan, R.J. (2019)
The sedimentary archive preserved at passive margins provides important clues about the evolution of continental topography. For example, histories of African uplift, erosion, and deposition of clastic sedimentary rock provide information about mantle convection. Furthermore, relating histories of uplift and erosion from regions where sediment is generated to measurements of efflux is important for understanding basin evolution and the distribution of natural resources. We focus on constraining Mesozoic to Recent solid sedimentary flux to northwest Africa's passive margin, which today is fed by rivers draining dynamically supported topography. Histories of sedimentary flux are calculated by mapping stratigraphy using seismic reflection and well data courtesy of Tullow Oil Plc and TGS. Stratigraphic ages, conversion from two-way time to depth and compaction, are parameterized using biostratigraphic and check-shot records from exploration, International Ocean Discovery Program and Deep Sea Drilling Project wells. Results indicate that Late Cretaceous to Oligocene (∼100–23 Ma) sedimentary flux decreased gradually. A slight increase in Neogene sedimentary flux is observed, which is concomitant with a change from carbonate to clastic sedimentation. Pliocene to Recent (∼5–0 Ma) flux increased by an order of magnitude. This history of sedimentary flux and facies change is similar to histories observed at other African deltas. To constrain sources of sedimentary flux, 14,700 longitudinal river profiles were inverted to calculate a history of continental uplift. These results were used to parameterize a simple “source-to-sink” model of fluvial erosion and sedimentary efflux. Results suggest that increased clastic flux to Africa's deltas from ∼30 Ma was driven by denudation induced by dynamic support.